Income source confusion using the SILC - Christopher R. Bollinger; Iva V. Tasseva (University of Essex, Institute for Social and Economic Research (ISER), 2022)
We use a unique panel of household survey data - the Austrian version of the European Union Statistics on Income and Living Conditions (SILC) for 2008-2011 - which have been linked to individual administrative records on both state unemployment benefits and earnings. We assess the extent and structure of misreporting across similar benefits and between benefits and earnings. We document that many respondents fail to report participation in one or more of the unemployment programmes. Moreover, they inflate earnings for periods when they are unemployed but receiving unemployment compensation. To demonstrate the impact of income source confusion on estimators we estimate standard Mincer wage equations. Since unemployment is associated with lower education, the reports of unemployment benefits as earnings bias downward the returns to education. Failure to report unemployment benefits also leads to substantial sample bias when selecting on these benefits, as one might in estimating the returns to job training.
Keywords: D31; C8; 330; income source confusion; survey and administrative data; measurement error